Analysis of combustion, performance and emission characteristics of a diesel engine using low sulfur tire fuel - Aydin, Huseyin; Ilkilic, Cumali (Elsevier Sci Ltd, 2015)
An alternative fuel for diesel engines was produced from waste vehicle tires by the method of pyrolysis. In order to reduce sulfur content of produced the liquid fuels, during the reaction Ca(OH)(2) was used. Then, H2SO4 were used after the reaction and the sulfur content of the product was reduced by 83.75%. The properties of diesel fuel, low sulfur tire fuel and fuel mixtures of low sulfur tire fuel and diesel fuel were found. Then the prepared fuel blends and diesel fuel were tested in a diesel engine. Performance, combustion and emission parameters of the engine when using each fuel were obtained and comparisons were made with D2 fuel. Power, torque and mean effective pressure, mass fuel consumption, effective efficiency and bscf values presented. Results justify that the performance of the engine slightly lowers by using blends of LSTF. Cylinder pressure and heat release rate values of the test fuels usage were quite similar with those of D2. CO, HC, and smoke emissions were slightly higher while NOx emissions were lower for LSTF blends. All of these results indicate that desulfurized tire fuels with low percentages can be used as alternative fuel in diesel engine. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Tire fuel; Diesel engine; Pyrolysis; Desulfurization